Analysis of spine motion during prehospital extrication procedures in motorsport - Uzun, Davut D.; Klein, Roman; Rittmann, Adrian; Häske, David; Schneider, Niko R. E.; Kreinest, Michael (European journal of trauma and emergency surgery, 2024)
The appropriate extrication techniques for trauma patients after car accidents remain a topic of controversy. Various techniques for immobilizing the cervical spine during prehospital extrication have been investigated.